1988
DOI: 10.1007/bf00441819
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome translocation (2;13) (q37;q14) in a disseminated alveolar rhabdomyosarcoma

Abstract: Chromosome analysis of tumour cells in the bone marrow of a 13.5-year-old girl (without a primary tumour) revealed a pseudo-diploid or pseudo-tetraploid karyotype with a translocation involving the long arms of chromosomes 2 and 13: t(2;13)(q37;q14). This finding enabled the diagnosis of a disseminated alveolar rhabdomyosarcoma (RMS) to be established. The patient was treated by cytotoxic chemotherapy, went into complete remission, but died of relapse 14 months after diagnosis. As several cases with this trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…This abnormality was first described by Seidal et al (1982) who found three copies of a marker, identified as t(2;13)(2pter-t2q37::13q14+13qter), in one of seven cases in which banding studies were possible. Numerous other authors have now reported the same translocation in a large number of cases of alveolar RMS (Turc-Care1 et al, 1986;Douglass et al, 1987;Lai et al, 1987;Lizard-Nacol et al, 1987;Rowe et al, 1987;Engel et al, 1988Wang-Wuu et al, 1988Vagner et al, 1989;Valentine et al, 1989;Nojima et al, 1990;Mitchell et al, 1991) ?p25 t(2;13)(p25;q14),t( 1;13)(q21;q14) (other than t with 2q o r 2p) t(1;13)(p36;q14) t(1;13)(p21;q14) t(8;13)(p21;q14) t(8; I l)(q22;q I3),t(X; I l)(q28;q 13) t(l;I l)(p13;q13) t(2; I l)(q37;q 13) t( I 1;22) t( I I ;22)(q24;q I2),ins t(5; 13) on chromosome 2 or 13: one case of t(2;11)(q37;q13) (Whang-Peng et al, 1986), one case of t(1;13)(p21;q14) (Douglass et al, 1987), one case of t(8;13)(p2l;q14) (Douglass et al, 1991), and four cases of t(1;13)(p36;q14) (Biegel et al, 1991;Douglass et al, 1991; patient JM, present work). The total percentage of cases with breakpoints at 2q37 is 68%, and at 13q14 it is 86%.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This abnormality was first described by Seidal et al (1982) who found three copies of a marker, identified as t(2;13)(2pter-t2q37::13q14+13qter), in one of seven cases in which banding studies were possible. Numerous other authors have now reported the same translocation in a large number of cases of alveolar RMS (Turc-Care1 et al, 1986;Douglass et al, 1987;Lai et al, 1987;Lizard-Nacol et al, 1987;Rowe et al, 1987;Engel et al, 1988Wang-Wuu et al, 1988Vagner et al, 1989;Valentine et al, 1989;Nojima et al, 1990;Mitchell et al, 1991) ?p25 t(2;13)(p25;q14),t( 1;13)(q21;q14) (other than t with 2q o r 2p) t(1;13)(p36;q14) t(1;13)(p21;q14) t(8;13)(p21;q14) t(8; I l)(q22;q I3),t(X; I l)(q28;q 13) t(l;I l)(p13;q13) t(2; I l)(q37;q 13) t( I 1;22) t( I I ;22)(q24;q I2),ins t(5; 13) on chromosome 2 or 13: one case of t(2;11)(q37;q13) (Whang-Peng et al, 1986), one case of t(1;13)(p21;q14) (Douglass et al, 1987), one case of t(8;13)(p2l;q14) (Douglass et al, 1991), and four cases of t(1;13)(p36;q14) (Biegel et al, 1991;Douglass et al, 1991; patient JM, present work). The total percentage of cases with breakpoints at 2q37 is 68%, and at 13q14 it is 86%.…”
Section: Discussionmentioning
confidence: 82%
“…G-banding of alveolar RMS was first reported in 1982 when Seidel et al observed three identical 2q markers, identified as t(2;13)(2pter+2q37::13q14-+13qter), in one of their seven cases of RMS-A. Since then, additional cases of the 2;13 translocation have been reported and this abnormality is commonly considered to be associated with RMS-A (Trent et al, 1985;Clayton et al, 1986Garvin et al, 1986Moriyama et al, 1986;Turc-Carel et al, 1986;Douglass et al, 1987;Lai et al, 1987;Lizard-Nacol et al, 1987;Rowe et al, 1987;Engel et al, 1988;Hayashi et al, 1988;Wang-Wuu et al, 1988).…”
Section: Introductionmentioning
confidence: 98%
“…Rearrangements of 2q, particularly t(2; 13) (q35+37;q14), are commonly observed in rhabdomyosarcoma (Seidal et al, 1982;Potluri and Gilbert, 1985;Garvin et al, 1986;Turc-Carel et al, 1986;Douglas et al, 1987;Lai et al, 1987;Lizard-Narcol et al, 1987;Rowe et al, 1987;Engel et al, 1988;Wang Wuu et al, 1988;Mitelman, 1991;Whang-Peng et al, 1992;Gladstone et a]., 1993). Abnormalities of the long arm of chromosome 2 were observed in both of the presented cases of malignant triton tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar histology was assigned based on morphology and upon identification of the t(2;13)(q37;q14) translocation, expressing the resulting PAX3-FOXO1 (formerly known as PAX3-FKHR) fusion protein (55). Although there was a time that the 2q breakpoint was assigned to q35 or q37, this has now been resolved as a q35 breakpoint, so that the translocation would now more correctly be stated as t(2;13)(q35;q14).…”
Section: Alveolar Rms Cell Linesmentioning
confidence: 99%